Developmental progression of mental state understandings in infancy. (July 2019) - Siu, Tik-Sze Carrey; Cheung, Him
This study establishes a sequence of developing mental state understandings in infants. We used three violation-of-expectation paradigms to assess fifty-seven 16-month-olds' ability to (a) infer an actress's intention from her prior repeated approaches to an object, (b) recognize her emotion by watching her facial-emotional display, and (c) deduce her false belief by noticing her lack of visual access to a change in the experimental setup. Contingencies between passing the three tasks were analyzed. Results showed that the infants made sense of intention first, followed by emotion, and then false belief. This progressive sequence parallels what has been found with preschoolers using verbal theory-of-mind tasks.